Implementation Of Legal And Human Rights Protection For Children And Disabilities - Juniarta Simamora; Junifer Dame Panjaitan (International Journal of Social Research, 2023)
This research explores the legal protection of children and persons with disabilities in Indonesia within the framework of human rights. The study assesses the implementation of Law No. 35 of 2014 concerning child protection and Law No. 8 of 2016 regarding disabilities. The constitutional context, incorporating human rights in the 1945 Constitution, sets the foundation for the protection of citizens' rights and obligations. While child protection laws exist, the increasing violations and challenges faced by children in various aspects of life underscore the need for an effective implementation mechanism. Additionally, the absence of derivative regulations for the Disability Law hampers its optimal enforcement, leading to uncertainties and potential rights violations for persons with disabilities. The study utilizes the Normative Juridical method, relying on secondary data through library research to analyze legal provisions and regulations. The results highlight the broad spectrum of legal protection for children, encompassing human rights, judicial processes, welfare, and protection from exploitation. Conversely, the research identifies shortcomings in the implementation of disability laws, emphasizing the crucial role of derivative regulations in ensuring effective protection for persons with disabilities. The conclusion emphasizes the need for improved government actions, collaboration, and the issuance of derivative regulations to enhance the practical realization of legal protections for both children and persons with disabilities.